PENGARUH KOMPETENSI APARATUR, KOMITMEN ORGANISASI, PARTISIPASI MASYARAKAT, AKUNTABILITAS, DAN TRANSPARANSI TERHADAP PENGELOLAAN KEUANGAN DESA - YUNI VERONIKA; Yesi Mutia Basri (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2023)
This study aims to determine at the effect of apparatus competence, organizational commitmen, community particpation, accountability, and transparancy on village financial management. The population in this study was 242 villages in Kampar Regency. The sample used was a sample of 71 villages with a total of 284 respondents using the propoportional stratified random sampling method. This study uses primary data using a questionnaire. The analytical method used in this research in linear multiple regression analysis. The analytical tool used in this study is Product Statistics and Service Solution (SPSS) version 21.0. The results of this study indicate that transparency, accountability, community participation, quality of human resources and village financial management.